Implementasi Konsep Authentic Space pada Interior Rumah Makan â€œAngkringanâ€ di Surabaya - Vebbe, Vebbe; Sitindjak, Ronald Hasudungan Irianto; Poillot, Jean Francois (Intra, 2017)
Nowadays, the food business more and more in demand, and it make increasingly fierce competition. Therefore, Â it need new innovations to increase the interest of the visitors, one of them with redesign innovation. Resto Park in Surabaya would like to redesign to be a restaurant that attracts consumers and is able to compete against the times. By using the concept of Angkringan as in Yogyakarta, is expected to attract the interest of visitors whether it is the original visitors of Surabaya or other immigrants outside Surabaya. With such ethnic nuances, Angkringan is expected to compete with other restaurants that carry the theme of this traditional ethnic modern.